Analysis of Student Satisfaction with the Google Site-Based Platform as a Media for Implementing Independent Study Tests in the Chemistry Education Study Program at Medan State University - Ardila, Mutia; Samosir, Rafidah Almira (Holistic Science, 2024)
This study aims to evaluate student satisfaction with the self-study platform based on Google Sites, which is used as a medium for conducting exams in the Chemistry Education Program at Universitas Negeri Medan. The research method employed is descriptive qualitative, with a sample of 107 respondents. The results of the study show that 64.5% of students stated that the platform was very easy to access, 53.3% liked its design, and 55.1% were satisfied with the registration information and exam implementation. The simulation feature also received positive feedback, with 68% stating that the platform was easy to access, 56% feeling helped by the platform, and 64% feeling more prepared to take the exam after completing the simulation. Based on the research findings, the level of satisfaction with the platform indicates very positive results in contributing to student readiness, although further development is still needed to improve the quality of the independent exam implementation services for students.